2015
DOI: 10.1002/lt.24030
|View full text |Cite
|
Sign up to set email alerts
|

Management of bleeding and transfusion during liver transplantation before and after the introduction of a rotational thromboelastometry–based algorithm

Abstract: Orthotopic liver transplantation (OLT) remains a potentially hemorrhagic procedure. Rotational thromboelastometry (ROTEM) is a point-of-care device used to monitor coagulation during OLT. Whether it allows blood loss and transfusions to be reduced during OLT remains controversial. Excellent correlations and predictive values have been found between ROTEM parameters and fibrinogen. We hypothesized that the use of a ROTEM-based transfusion algorithm during OLT would lead to more fibrinogen transfusion and decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 28 publications
(36 reference statements)
1
64
0
1
Order By: Relevance
“…In the single trial evaluating the influence of fibrinogen administration on blood transfusion in LT, an observational study by Roullet and coworkers (15) found that a thromboelastometry-based algorithm led to increased fibrinogen transfusion; however, like us, they saw no decrease in blood transfusions. To our knowledge, ours is the only completed randomized trial to assess the efficacy of preemptive fibrinogen administration in LT.…”
mentioning
confidence: 51%
“…In the single trial evaluating the influence of fibrinogen administration on blood transfusion in LT, an observational study by Roullet and coworkers (15) found that a thromboelastometry-based algorithm led to increased fibrinogen transfusion; however, like us, they saw no decrease in blood transfusions. To our knowledge, ours is the only completed randomized trial to assess the efficacy of preemptive fibrinogen administration in LT.…”
mentioning
confidence: 51%
“…Manuscript not available for reading. Contact information of corresponding author not available.Karkouti 2016 [61]Cardiac surgeryStepped-Wedge Clustered RCTLevin 2014 [62]Cardiac surgeryFocus on protamine-administrationLier 2009 [63]TraumaReviewMallaiah 2015 [64]Obstetric haemorrhageBefore-after trialManikappa 2011 [65]Cardiac surgeryWhole blood transfusionsMessenger 2011 [66]TraumaProspective cohort studyMishra 2015 [67]Cardiac surgeryFocus on platelet function testingNaik 2015 [68]Major spinal surgeryNon-randomisedPetricevic 2013 [69]Cardiac surgeryObservational trialRahe-Meyer 2009 [70]Aortic surgeryNon-randomisedRoullet 2015 [71]Orthotopic liver transplantationNon-randomisedSmart 2015 [72]Orthotopic liver transplantationRetrospective non-randomised trialStancheva 2011 [73]Orthotopic liver transplantationObservational trialTarabarin 2013 [74]Bile duct surgeryPossibly relevant. Manuscript not available for reading.…”
Section: Resultsmentioning
confidence: 99%
“…Transfusion algorithm was based on core lab and ROTEM results as already described 6. Tranexamic acid (TXA) administration was guided by typical ROTEM traces of hyperfibrinolysis (EXTEM ML >15%),14 15 and/or oozing in the surgical field with no macroscopic clot formation and/or bleeding exceeding one blood volume.…”
Section: Methodsmentioning
confidence: 99%